2004
DOI: 10.1111/j.1479-8425.2003.00062.x
|View full text |Cite
|
Sign up to set email alerts
|

Cephalometric analysis parameters related to the severity of sleep-breathing disorders

Abstract: The purpose of this study is to demonstrate the cephalometric parameters of craniomandibular characteristics, which are indicators of the severity of sleep-breathing disorders (SBD). Eighty-eight subjects who were evaluated by using all-night polygraphy (PSG) and underwent a lateral cephalogram were included. We used logistic regression analysis to determine the cephalometric parameters. The apnea-hypopnea index (AHI), respiratory related arousal (RERA), and 90% > SpO 2 were applied to the severity of SBD as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Previous studies using single morphology have suggested the following parameters as risk indicators of OSAHS: small jaw, 2,6,9 long pharynx, 14 retrognathia, 6,11 and decreased facial axis 25,26 in skeletal morphology; and increased soft palate and tongue area 10,11,27 in soft tissue morphology. Another study showed that tongue volume is correlated with BMI, 19 which can identify the risk factor of OSAHS with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using single morphology have suggested the following parameters as risk indicators of OSAHS: small jaw, 2,6,9 long pharynx, 14 retrognathia, 6,11 and decreased facial axis 25,26 in skeletal morphology; and increased soft palate and tongue area 10,11,27 in soft tissue morphology. Another study showed that tongue volume is correlated with BMI, 19 which can identify the risk factor of OSAHS with obesity.…”
Section: Discussionmentioning
confidence: 99%